PENERAPAN FITUR ADAPTIVE MULTI RATE (AMR) PADA JARINGAN GSM - Syarif, Abdusy; Fachril, Ahmad (Bina Nusantara University, 2010)
Adaptive Mutlirate (AMR) is a feature that plays an important role in the efficiency of use of cell/voice channels and GSM networks in overall and it can improve sound quality dynamically based on actual measurements (real time) between Mobile Station (MS) and Base Transmitter Station (BTS). Resources used as analytical parameters are SQI (Speech Quality Index), MOS (Mean Opinion Score) and the sound quality on the network without and with AMR. Measurements using Test Equipment Mobile System (TEMS) while locking devices to the single channel and comparing them between the two types of network. Based on test results it is obtained that with voice channels with AMR can increase the value of SQI approximately 40% for fullrate channels and about 60% for half-rate channels producing a remarkable (excellent) level, with research and further measuring it is expected to produce better and more perfect sound quality.Kata kunci: AMR, SQI, GSM networkABSTRAK